(untitled) (Research, Society and Development, 2021)
The feline leukemia virus (FeLV) has a worldwide distribution and in domestic cats the main source of transmission occurs through saliva. Thus, direct or indirect contact between animals is a major cause for the spread of this virus. There are few data in the literature that direct the number of positive animals in Espírito Santo, Southeastern Brazil. Therefore, the objective was to carry out a survey of the prevalence of positive FeLV domestic cats to evaluate the hematological parameters present in these infected animals, as well as the tutors’ knowledge about the disease. Seventy medical records of domestic cats tested for FeLV were analyzed, from January 2020 to December 2020 and were attended at the Veterinary Hospital of Universidade Vila Velha. Domestic cats were diagnosed using the SNAP® FIV / FeLV Combo. Hematological data were obtained by means of blood count and serum biochemistry tests. The results showed an occurrence of 42.6% of FeLV positive animals, with males being more affected (18/30; 60%; P<0.05) and animals with access to the street (14/30; 46.7%; P <0.05). All positive animals showed some hematological alteration, such as anemia, thrombocytopenia, neutrophilia and lymphopenia. It was concluded that the occurrence of FeLV in cats in Vila Velha, Espírito Santo is high, and measures should be taken to intensify the control and prophylaxis measures against this disease.